Correlation between shopping addiction and negative emotions and general satisfaction with health and lifestyle status - Nina Eraković; Šemsudin Porčić; Mira Spremo (Биомедицинска истраживања, 2020)
Introduction: According to previous studies, compulsive buying is the problem in the world today by means of which a large number of people, especially women, face their problems in everyday life and functioning. The aim of the paper is to investigate whether or not there is a correlation between shopping addiction, emotions, and stress and general satisfaction with health and lifestyle. Methods: The study included a hundred respondents belonging to female population. The following tests were used: The Screening Test for Compulsive Buying for compulsive buying, DASS test (depression, anxiety and stress) for negative emotions and the World Health Organization questionnaire - WHOQOL-BREF, including physical and mental health, social interactions and the environment. Results: The study showed statistically significant correlations between: compulsive buying and anxiety (r=.236, p<0.01), compulsive buying and depression (r=.360, p<0.01), and compulsive buying and stress (r=.378, p<0.01). The WHOQOL-BREF test results showed that there was a negative correlation between compulsive buying and physical health (r=-.253, p<0.05), there was no statistically significant correlation between compulsive buying and mental health. There was a significant negative correlation between compulsive buying and social interactions (r=-.355, p<0.01) and between compulsive buying and the environment (r=-.430, p<0.01). Conclusion: Women who are more likely to experience compulsive buying develop negative emotions such as anxiety and depression more frequently. They show a stress response more often, feeling less healthy, their social interactions and functioning in the social environment are much more disturbed compared to women who buy less.
Keywords: compulsive buying; anxiety; depression; health; stress